Effect of pre-germination seedling depth on growth rates of rice - Ali, Mohammad Zuhairi; Muhammad Nasir, Rezki Afrina; Mohamed Noh, Mohd Fakaruddin; Mohd Zin, Hakim; Langidai, Steven Lun; NasMaznan, Mohammad Hairun; Azman, Elisa Azura (International Journal of Agriculture Innovation and Research, 2021)
The current practice of farmers is using seed blower to broadcast the rice seeds on the rice field and the depth of planting pre-germination seedling has a meaningful effect on the growth of rice seed. Therefore, the objective of this study was to determine the effect of pre-germination seedling depth on the growth rate. The study was conducted in Ladang 10, Universiti Putra Malaysia. The rice variety used was MARDI Siraj 297. The rice seeds were exposed to 5 treatments of depth in the soil; T1: 0 cm, T2: 1 cm, T3: 2 cm, T4: 3 cm, T5: 4 cm with five replication arranged in Completely Randomized Design (CRD). The data of growth rate was recorded 14 days after planting. The study showed that the rice seeds exposed at 0 cm treatment were significantly different in the percentage of growth of 95.6% compared to other treatments. The seed germination was reduced as the planting depth increased and it is represented in the equation percentage of Growth = -15.36 planting depth + 91.92 (R2 = 0.9681). Therefore, seed broadcasting using a seed blower to the soil in saturated conditions can result in the pre-germination seeds sinking and dying. Eventually, planting pre-germinated rice seeds at a depth of one (1) cm or more will reduce the number of plants per m2 and affect grain yield.